Assessment of the nutritional profile of Crossfit Practitioners (Research, Society and Development, 2024)
CrossFit® functional training has been gaining popularity, with its varied "Workouts of the Day" (WOD) becoming a common practice. The training sessions are characterized by their high physical demand, which is widely adopted by tactical athletes although, there is still little information about the factors that influence performance in CrossFit ®. This literature review aims to identify the dietary factors and nutritional profile of CrossFit® performance and the factors that can maximize performance. The present study was carried out through a bibliographic literature review, in which scientific documents and official documents from National and International Health Organizations were used and articles published in the last ten years (2014-2024) in Portuguese and English were selected. The databases researched were SCIELO, PUBMED, and EBSCO, which identified predominant diets among practitioners and factors that contribute to improved performance such as sleep, water intake, and supplementation. The articles analyzed present varied results and no specific parameter that stands out as a universal highlight, in association with performance in CrossFit®, regardless of the WOD. However, some studies indicate that competitive experience combined with body composition can influence performance, while studies on supplementation do not present consistent evidence to confirm its effectiveness, highlighting the need for further longitudinal studies for greater clarification.